2019
DOI: 10.1016/j.jmr.2019.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Improved waveguide coupling for 1.3 mm MAS DNP probes at 263 GHz

Abstract: We consider the geometry of a radially irradiated microwave beam in MAS DNP NMR probes and its impact on DNP enhancement. Two related characteristic features are found to be relevant: (i) the focus of the microwave beam on the DNP MAS sample and (ii) the microwave magnetic field magnitude in the sample. We present a waveguide coupler setup that enables us to significantly improve beam focus and field magnitude in 1.3 mm MAS DNP probes at a microwave frequency of 263 GHz, which results in an increase of the DNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 81 publications
0
22
1
Order By: Relevance
“…We note however that the enhancement values at 18.8 T have been obtained in 1.3 mm rotors where the microwave eld distribution is more favorable than in 3.2 mm rotors. 48 Additionally, we have shown that depolarization effects are reduced at fast MAS in these shortlinked binitroxides, while the favorable electron relaxation times of AMUPol are preserved.…”
Section: Discussionmentioning
confidence: 85%
“…We note however that the enhancement values at 18.8 T have been obtained in 1.3 mm rotors where the microwave eld distribution is more favorable than in 3.2 mm rotors. 48 Additionally, we have shown that depolarization effects are reduced at fast MAS in these shortlinked binitroxides, while the favorable electron relaxation times of AMUPol are preserved.…”
Section: Discussionmentioning
confidence: 85%
“…This microwave-induced heating is especially large for conductive samples. It also increases with increasing microwave power, which limits the maximal microwave power, which can be employed in practice [178]. Furthermore, the imaginary part of the permittivity usually increases at higher frequencies and hence, the heating due to microwave is increased for DNP at higher B0 field.…”
Section: Microwave Source and Microwave Powermentioning
confidence: 99%
“…In contrast, the combination of solid-state µw sources that allow for more versatile and rapid time-domain (as opposed to frequency-domain) manipulation of µw phase and frequency, in conjunction with a broad-band amplifier would be most beneficial. Optimization of µw transmission pathway, 52,53 optimization of NMR rotor dimensions, 35 and addition of resonator or lens to maximize µw intensity at the sample position will further increase the B 1 power generated with the given µw power available, and hence further enhance the capacity of AWG-DNP, especially at higher field and temperatures. This study paves the way for time-dependent AWG µw manipulated MAS-DNP that has the prospect to become a mainstay of DNP.…”
Section: Discussionmentioning
confidence: 99%